Useful Role of a New Generation of Dexamethasone, Vitamin E and Human Serum Albumin Microparticles in the Prevention of Excitotoxicity Injury in Retinal Ocular Diseases - Javier Rodríguez Villanueva; Pedro de la Villa; Rocío Herrero-Vanrell; Irene Bravo-Osuna; Manuel Guzmán-Navarro (MDPI AG, 2024)
Excitotoxicity has been linked to the pathogenesis of several serious degenerative ocular diseases. Long-term overactivation of the NMDA receptor by glutamate in retinal ganglion cells (RGCs) results in degeneration, apoptosis and loss of function leading to blindness. NMDA receptor antagonists have been proposed as a pharmacological blockage of glutamate excitotoxicity. However, an inhibition of the pathway activated by glutamate receptors has intolerable side effects. An interesting pharmacological alternative would be the use of antiapoptotic compounds as RGCs' neuroprotective active substances. Several mechanisms have been proposed to explain neuroprotection, including anti-inflammatory and scavenging activities. Here, the role of dexamethasone in neuroprotection was studied. For this purpose, original controlled release systems composed of microparticles containing dexamethasone with or without vitamin E and human serum albumin (HSA) were designed. The particles were prepared by the solid-in-oil-in-water (S/O/W) emulsion-evaporation technique. After properly characterization of the particles, they were intravitreally injected into an rat model of acute ocular excitotoxicity injury. The functionality of the retina was determined by electroretinography and RGCs were counted after cell immunohistochemistry. These microparticulate systems showed the ability to maintain normal electroretinal activity and promoted significant protection of RGCs. Through this proof of concept, we demonstrated that dexamethasone could be a useful anti-inflammatory agent to avoid the progression of degenerative ocular diseases. Furthermore, when administered in controlled release systems that provide low concentrations during prolonged periods of time, not only can the patient's comfort be increased but the cytotoxicity of the drugs can also be avoided.